Analisis Penerapan K3 pada Proyek Pembangunan Gedung Instalasi Rawat Jalan RSUD Abadi Samboja Kutai Kartanegara - Widayani, Heni Ratna; Anggitasari, Inge (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study was conducted to analyze the implementation of Occupational Safety and Health (OSH) at the construction project of the Outpatient Installation Building of RSUD Abadi Samboja, Kutai Kartanegara Regency. The objective of the study is to determine the effectiveness of OSH implementation based on five main aspects: the use of Personal Protective Equipment (PPE), emergency preparedness, structural work, electrical work, and workplace health and hygiene. The method used is a quantitative approach with univariate analysis involving 52 project worker respondents. The results showed that the overall OSH implementation achieved an effectiveness level of 89.7%, which falls under the